The Influence of Land and Building Tax (PBB), Duty on the Acquisition of Land and Building Rights (BPHTB), and Groundwater Tax (PAT) on Regional Original Revenue at the Regional Revenue Agency of Bandung City - Fauzi, Afrizal Iga; Kustinah, Siti (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study seeks to assess the collective impact of PBB, BPHTB, and PAT on the PAD of Bandung City during the 2020–2024 period. The phenomenon underlying this research is the trend of increasing PAD targets and realizations in Bandung City each year, while the revenue from each type of regional tax has shown fluctuations during the same period. The data used are monthly tax realization data obtained from the Bandung City Regional Financial and Asset Agency through documentation techniques and literature study. The investigation applies a numerical research strategy incorporating descriptive characterization and relational analysis. Data processing is conducted through the application of multiple linear regression techniques, assisted by SPSS release 25. The outcomes demonstrate that land and building tax as well as duty on the acquisition of land and building rights contribute positively and significantly to regional own-source revenue, whereas entertainment tax does not produce a statistically meaningful influence. Simultaneously, the three types of taxes have a significant influence, explaining 88.8% of the variation in PAD. These findings emphasize the importance of integrated management and strategies to optimize regional tax revenue to strengthen the fiscal independence of Bandung City.